2009
DOI: 10.1136/bjo.2008.145862
|View full text |Cite
|
Sign up to set email alerts
|

Polypoidal choroidal vasculopathy and late geographic hyperfluorescence on indocyanine green angiography

Abstract: LGH is a highly sensitive and specific ICGA finding for the diagnosis of PCV. Increased surveillance should be implemented in eyes in which LGH persists after PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 25 publications
(26 reference statements)
0
26
0
Order By: Relevance
“…Observations of the corresponding uniform hyperfluorescent area within the late staining pattern (LGH) 15 in the area of the fine vascular network may indicate a relative leakiness of these crowded vessels, On the other hand, the LGH tended to become more obscure after the regression of the fine vascular network. However, the LGH was not detected as frequently in our eyes as Kang et al reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Observations of the corresponding uniform hyperfluorescent area within the late staining pattern (LGH) 15 in the area of the fine vascular network may indicate a relative leakiness of these crowded vessels, On the other hand, the LGH tended to become more obscure after the regression of the fine vascular network. However, the LGH was not detected as frequently in our eyes as Kang et al reported.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reducing the number of recurrences is an important aspect of the treatment of PCV. 13,14 Although there is no established way to predict recurrences, the indocyanine green angiographic (IA) findings seemed to offer some clues as was suggested by Kang et al 15 They investigated the staining pattern in late phase IA images and found a late geographic hyperfluorescent (LGH) pattern, which matched the total area of the branching network and polyps. They found that a persistence of the LGH pattern was associated with the recurrence of the polypoidal lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When ICGA could not be used for a definitive diagnosis owing to the presence of extensive subretinal hemorrhage, ICGA images obtained within 6 months of the initial diagnosis were reviewed. In some cases, the presence of late geographic hyperfluorescence on ICGA 17,18 and/or the doublelayer sign on optical coherence tomography (OCT) 18,19 was observed in association with a branching vascular network on ICGA. These cases were diagnosed as PCV, although no definite polypoidal lesion was identified.…”
Section: Introductionmentioning
confidence: 97%
“…5 Other features of PCV may include branching vascular network (BVN), pulsatile polyp, presence of hypofluorescent halo, and late phase hyperfluorescent plaque. 4,6,7 The location and size of polyps in ICGA are important features for surgeons to decide the area of thermal laser application or photodynamic therapy (PDT) because of the higher regression rate of polyps by PDT comparing with monotherapy with antivascular endothelial growth factor (anti-VEGF). 6 However, diagnosis of polyps in ICGA remains a challenge.…”
Section: Introductionmentioning
confidence: 99%